1999
DOI: 10.4141/p98-010
|View full text |Cite
|
Sign up to set email alerts
|

Annual legumes as green manure and forage crops in winter canola (Brassica napus L.) rotations

Abstract: . 1999. Annual legumes as green manure and forage crops in winter canola (Brassica napus L.) rotations. Can. J. Plant Sci. 79: 19-25. Cropping systems that reduce chemical fertilizer N requirements in winter canola (Brassica napus L.) need further study. Studies were conducted in 1994/1995 and 1995/1996 at two locations in Michigan i) to quantify the N accumulated at plowdown by berseem clover (Trifolium alexandrinum L.), alfalfa (Medicago sativa L.) and three annual medic species (Medicago truncatula Gaertn.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In western Montana, berseem clover produced greater herbage plowdown N than an annual alfalfa, however, N uptake in the following barley (Hordeum vulgare L.) crop was less (Westcott et al 1995). Shrestha et al (1999) reported that berseem clover managed as forage had a similar amount of plowdown N compared to alfalfa managed as a forage.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In western Montana, berseem clover produced greater herbage plowdown N than an annual alfalfa, however, N uptake in the following barley (Hordeum vulgare L.) crop was less (Westcott et al 1995). Shrestha et al (1999) reported that berseem clover managed as forage had a similar amount of plowdown N compared to alfalfa managed as a forage.…”
mentioning
confidence: 99%
“…Legume harvest management has been shown to have a major effect on the ability of legumes to contribute N to the soil (Sheaffer et al 1989;Shrestha et al 1999). Hesterman et al (1986Hesterman et al ( , 1987 determined that the biologically fixed N contribution of a one-cut system incorporated in the fall resulted in 37% greater N than a three-cut system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In areas with adequate rainfall, such as the Parkland and Boreal regions of Alberta, forage legumes offer potential to provide both forage yield and green manure benefits. Berseem clover provided similar benefit to a subsequent crop when managed solely as a green manure or when harvested once for forage and regrowth was ploughed down (Westcott et al 1995;Shrestha et al 1999).…”
mentioning
confidence: 89%
“…(Blackshaw et al 2001). A few green manure studies in Canada and northern USA have included annual clover species (Westcott et al 1995;Shrestha et al 1999;Bullied et al 2002), but further research is needed.…”
mentioning
confidence: 99%